Answer:
an = -6n + 5.
Step-by-step explanation:
This is an arithmetic sequence with first term a1 = -1 and common difference d = -6
an = a1 + d(n-1)
an = -1 + -6(n - 1)
an = -1 -6n + 6
an = -6n + 5.
What is the separate weight
Given that Allison’s dog is 6 pounds more than 5 times the weight of Gail’s dog, it is important to know the following:
1. The word "more" indicates an Addition.
2. The word "times" indicates Multiplication.
Knowing this, you can write the following expression to represent "5 times the weight of Gail’s dog", where "g" is the weight of Gail’s dog:
Therefore, you can determine that the weight of Allison's dog (in pounds) is the sum of 6 pounds and 5 times the weight of Gail's dog (in pounds). Then, you can represent this with this algebraic expression:
Hence, the answer is:
Your answer is b because the common denominator is 10 and so just look at my pic
Answer:
10
Step-by-step explanation: